Contemporary Problems of Sciences in the View of Unitary Quantum Theory (Global Journal of Science Frontier Research, 2013)
The present article discuses the problems of new Unitary Quantum Theory in its applications to the different aspects of the reality. There are spectacular examples of such applications.
Keywords: unitary quantum theory; standard model; quantum electrodynamics; maxwell equations; schro-dinger equation; solid state physics; zone theory; semicondu